Biopsychosocial factors associated with symptom severity in the overlap of non-erosive reflux disease and epigastric pain syndrome: A multicenter cross-sectional study - Mi Lv; Hui Che; Jiayan Hu; Wenxi Yu; Zhaoxia Liu; Xiaolin Zhou; Binduo Zhou; Jinyi Xie; Fengyun Wang (PLoS ONE, 2025)
Background The overlap between non-erosive reflux disease (NERD) and epigastric pain syndrome (EPS, a subtype of functional dyspepsia) is common, yet its associated factors remain poorly defined. We aimed to identify factors associated with symptom severity in NERD-EPS overlap, focusing on psychosocial and somatic factors. Methods In this multicenter cross-sectional study, 800 patients meeting Rome IV criteria for NERD-EPS overlap were enrolled. Standardized questionnaires assessed gastrointestinal symptoms (GSRS), somatic symptoms (PHQ-15), anxiety/depression (PHQ-4), and sleep quality (SRSS). Multivariable regression models identified factors independently associated with GSRS scores, adjusted for demographics and clinical covariates. Interaction terms were tested to assess whether the association between one factor and GSRS scores varied across different levels of another factor. Results Of the 800 patients, 67% were female, and the mean age was (44.50 ± 14.43) years. 67% had mild or more sleep problems, and 47% had anxiety or depression. Somatic symptoms (PHQ-15) showed the strongest association with GSRS scores (β = 0.617, P < 0.001), followed by poor sleep quality (SRSS; β = 0.115, P < 0.001) and anxiety/depression (PHQ-4; β = 0.069, P = 0.026). Urban residence (β = 0.071) and mixed labor type (β = −0.066) were also independently associated with symptom burden. Conclusion Somatic symptoms, psychological distress, and sleep disturbances were the factors most strongly associated with symptom severity in NERD-EPS overlap, with additional contributions from younger age, male sex, and urban residence. Our findings advocate for integrated biopsychosocial interventions to alleviate symptom burden in this population.